Analisis Strategy Pengembangan Bisnis E-Commerce Pertamina Retail dengan Pendekatan Bisnis Model Kanvas - Latief, Prori Vitaliano; Syarief, Rizal; Hasbullah, Rokhani (Institut Pertanian Bogor, 2019)
The competition of oil and gas industri in Indonesia is very tight. To get survive from the competition; the company has to develop their technology. Nowadays, technological advancement have salient roles in improving the company's business. PT Pertaminan Retail is a large oil and gas company in Indonesia. This study analyzed the design of e-commerce business development models from PT Pertamina Retail called MyPertamina. The method of the study is descriptive analysis and using business model canvas (BMC), the Delphi method, SWOT (Strenghts, weakness, opportunities, & threats), and the Blue Ocean Strategy. The datas in this study were secondary dan primary data. The secondary data obtained from the literature study and the primary data was by interviewing six informants. The research period starts from November to December 2018. The results of mapping the initial business model that used BMC, showed several aspects such as: customer segments, value propositions, channels, revenue streams, key resources, key activities, key partners, and costs structure. Environmental analysis used the Delphi method and the result was key trend value was 25.48%, industri strength was 25.19%, market strengths was 24.78%, and macroeconomic strengths was 24.55%. MyPertamina's internal environment influenced by product aspects, infrastructure management, customer interface, and financial aspect. The results of the SWOT analysis of nine BMC unsurts showed that the highest strength was the key partnership and the lowest strength was customer relationship. Meanwhile, the biggest opportunity was value proposition and the lowest opportunity was cost structure. The highest threat was customer segment, and the lowest threat was key partners. The business development model in this research focused on customer segment, key partnership, and value proposition, unsurts developed using the blue ocean strategy method.